Health Education through Audio Visual Media Effects on Increasing Stunting Prevention Knowledge in Pre-Marriage Couples in Cimahi - Nurhayati, Fitri; Azzahra, Destiara; Lestari, Mega Dewi (Devotion : Journal of Research and Community Service, 2023)
One of the big problems currently occurring in child development is stunting. The prevalence of stunting under five in West Java in 2021 is 24.5%, and in Cimahi City in 2022 it is 9.88%. Prevention of stunting can be done for pre-marital couples. Audio Visual media is an effective medium for increasing knowledge about stunting prevention. The purpose of this study was to determine the effect of health education through audio-visual media on increasing knowledge about stunting prevention in pre-marital couples in the work area of the Ministry of Religion, Cimahi City in 2022. The type of research used was quasi-experimental with a one-group pre-test-post-test design. The sample of this study was 30 pre-married people in the working area of The Ministry of Religion, Cimahi City 2022. Data collection used a questionnaire with the intervention of audio-visual media. Univariate and bivariate analyzes were carried out using the Wilcoxon Sign Rank. The results of the study stated that there was an increase in the median before (1.00) and after (2.50) the intervention, and there was an effect of health education through audio-visual media on increasing knowledge about stunting prevention in premarital couples (p value 0.000). There is influence of health education through audio-visual media on increasing knowledge about stunting prevention in pre-marital couples in the work area of the Ministry of Religion, Cimahi City in 2022. Suggestions for midwives, audio-visual media that have been created by researchers can be used to increase pre-marital couples' knowledge about stunting prevention.